141 The rest and stress relationships between myocardial function, blood flow and energetics in type 2 diabetes. (6th June 2022) - Chowdhary, Amrit; Javed, Wasim; Thirunavukarasu, Sharmaine; Jex, Nicholas; Kotha, Sindhoora; Xue, Hui; Kellman, Peter; Swoboda, Peter; Greenwood, John P; Plein, Sven; Cubbon, Richard; Levelt, Eylem
Abstract : Background: Coronary microvascular dysfunction (CMD) and compromised cardiac energy production have been proposed as pivotal features underpinning diabetic cardiomyopathy. However, the relative contribution of these two factors to the subclinical functional alterations in type 2 diabetes (T2D) has not been reported. Objectives: Using cardiovascular magnetic resonance (CMR) and 31phosphorus MR spectroscopy (31P-MRS) we assessed changes in cardiac energetics, perfusion, global longitudinal strain, and systolic and diastolic function in response to dobutamine stress in T2D patients, non-athletic healthy volunteers (HV) and veteran athletes (VA). Methods: Thirty-six T2D patients, 12 VA and 20 HV were recruited. For the stress protocol, intravenous Dobutamine infusion was started at a dose of 10 μg/kg/min and titrated to a maximum dose of 40 μg/kg/min to achieve a target heart rate of 65% of the age-predicted maximum, with ECG and blood pressure (BP) monitoring. Mean rate pressure product was recorded at rest and stress. Target heart rate was maintained for the 31P-MRS and dobutamine stress CMR cine, mitral in-flow and perfusion acquisitions. Triglyceride Index (Tyg-I) was calculated as a measure of insulin resistance. Results: Demographic, biochemical and MRI data are shown in Table 1. Study groups had similar age and sex distribution with no known cardiovascular disease. Resting energetics was significantly lower in the T2D group compared to the VA and HV. Resting PCr/ATP was significantly lower in T2D patients compared to both control groups. Increases in RPP with dobutamine stress were similar across study groups. Significant reductions in myocardial PCr/ATP in response to acute stress were detected in HV and VA with similar percentage change from rest to stress as seen in T2D patients. The rest and stress left ventricular ejection fractions (LVEF) were similar across study groups. However, GLS and mitral in-flow E/A ratios were decreased in T2D at rest. During dobutamine stress, all groups showed similar increases in GLS and similar decreases in mitral in-flow E/A ratio, but these parameters remained higher in the controls. The stress MBF was significantly lower, and the NTproBNP and Tyg-I were higher in the T2D group.The correlations between the cardiac parameters are shown in Fig 1. Rest and stress LVEF correlated significantly with rest and stress MBF. There was no significant correlation between perfusion parameters and diastolic function. Contrary to this, while rest and stress energetics correlated with rest and stress E/A ratios, there was no significant correlation between energetics and LVEF. Suggesting a close relationship between insulin resistance, myocardial energetics and diastolic function, Tyg-I correlated with rest and stress PCr/ATP and rest and stress E/A. In multiple linear regression analysis, the HbA1C was significantly associated with stress MBF (ß= -0.02, p=0.0007). Conclusion: T2D patients show reductions in PCr/ATP, GLS and diastolic function at rest. In response to dobutamine stress, all three groups show similar decrements in myocardial energetics and diastolic function, and similar increments in GLS and LVEF, but with a blunted increment in stress MBF in T2D patients. HBA1c is a predictor of the stress MBF, and rest and stress LVEF show significant associations with rest and stress MBF. Significant associations were detected between the rest and stress energetics and diastolic function, possibly suggesting that diastolic function is a more energetically sensitive process. Conflict of Interest: Nil